2018
DOI: 10.3390/genes9070346
|View full text |Cite
|
Sign up to set email alerts
|

The Genetics of a Behavioral Speciation Phenotype in an Island System

Abstract: Mating behavior divergence can make significant contributions to reproductive isolation and speciation in various biogeographic contexts. However, whether the genetic architecture underlying mating behavior divergence is related to the biogeographic history and the tempo and mode of speciation remains poorly understood. Here, we use quantitative trait locus (QTL) mapping to infer the number, distribution, and effect size of mating song rhythm variations in the crickets Laupala eukolea and Laupala cerasina, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 112 publications
2
19
0
Order By: Relevance
“…This possibility is consistent with the results of multiple quantitative trait locus (QTL) studies done in cricket species from the genus Laupala, which identified genomic regions associated with mating song rhythm variations and female acoustic preference 71 . The 179 scaffolds that the authors reported being within one logarithm of the odds (LOD) of the seven QTL peaks, contained five pickpocket genes, three of them from class V and two from class IV.…”
Section: Pickpocket Gene Expansionsupporting
confidence: 88%
“…This possibility is consistent with the results of multiple quantitative trait locus (QTL) studies done in cricket species from the genus Laupala, which identified genomic regions associated with mating song rhythm variations and female acoustic preference 71 . The 179 scaffolds that the authors reported being within one logarithm of the odds (LOD) of the seven QTL peaks, contained five pickpocket genes, three of them from class V and two from class IV.…”
Section: Pickpocket Gene Expansionsupporting
confidence: 88%
“…; Blankers et al. ). The fact that only carrier frequency and not pulse rate has X‐linked QTL is particularly puzzling, especially in the light of strong signatures of X‐linkage for pulse rate in reciprocal interspecific hybrids.…”
Section: Discussionmentioning
confidence: 98%
“…In Drosophila melanogaster , expression of ATPα2 is limited to larval imaginal discs and adult male testes and accessory glands; RNAi and P-element knock-outs of the gene are homozygous viable but male-sterile (http://www.flybase.org/reports/FBgn0267363). Furthermore, we failed to recover an ortholog of ATPα2 from the Locusta migratoria genome assembly [47], and several other Orthopteran assemblies [48,49], suggesting that the ATPα1/α2 duplication may have arisen after the split of Orthopterans from the other insects we have surveyed ( Figure 1A ). We thus decided to focus on ATPα1, which shows clear orthology across taxa and a strong correlation between evolution at known cardenolide-sensitivity sites in the protein and specialisation on cardenolide-containing Apocynaceae plants [30].…”
Section: Methodsmentioning
confidence: 99%